Konsep Kepemimpinan Spiritual di Lembaga Pendidikan Islam: Analisis Library Research - Agus Faisal Asyha (Indo Publishing, 2026)
Islamic education requires leadership that focuses not only on academic aspects but also on the formation of students' character and ethics. One important concept in the management of Islamic educational institutions is spiritual leadership. This study aims to identify and analyze the existing literature on spiritual leadership in the context of Islamic education. This literature review uses a thematic analysis approach to explore the key dimensions of spiritual leadership, the factors influencing its implementation, and the implications arising from the application of spiritual leadership in Islamic educational institutions. The main findings of this study indicate that spiritual leadership involves moral, ethical, and religious vision dimensions, which are crucial in shaping students' character and creating an educational environment based on Islamic values. The study also identifies factors such as the quality of leaders and the involvement of all institutional members in the implementation of spiritual leadership. This review contributes to the development of leadership theory in Islamic education and underscores the importance of integrating spiritual values into educational practices. The implications of this research emphasize the importance of educational leaders with a clear spiritual vision to create institutions that excel not only academically but also in the formation of students' character.